2023
DOI: 10.1177/23259671231166371
|View full text |Cite
|
Sign up to set email alerts
|

Return to Preinjury-Level Sports After Arthroscopic Latarjet for Recurrent Anterior Shoulder Instability in Professional Athletes

Abstract: Background: The Latarjet procedure is recommended to treat recurrent anterior shoulder instability with glenoid bone loss. Longer return-to-sport (RTS) times have been reported after the open Latarjet when compared with the arthroscopic Latarjet. Purpose: To assess the clinical outcomes and RTS in athletes who underwent an arthroscopic Latarjet. Study Design: Case series; Level of evidence, 4. Methods: This study included 46 professional athletes with recurrent anterior shoulder instability who underwent an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Because the postoperative shoulder stability and sports level following salvage LP might be inferior to that following primary LP. Furthermore, numerous studies had also confirmed that primary LP can achieve excellent clinical outcomes for high-risk shoulder instability patients and physically active people [ 13 , 41 ]. Surgeons should conduct a comprehensive preoperative assessment of shoulder instability risks and perform the primary stabilization procedure on individual basis, thereby maximizing the potential benefits for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because the postoperative shoulder stability and sports level following salvage LP might be inferior to that following primary LP. Furthermore, numerous studies had also confirmed that primary LP can achieve excellent clinical outcomes for high-risk shoulder instability patients and physically active people [ 13 , 41 ]. Surgeons should conduct a comprehensive preoperative assessment of shoulder instability risks and perform the primary stabilization procedure on individual basis, thereby maximizing the potential benefits for patients.…”
Section: Discussionmentioning
confidence: 99%